Taxing Publicly Traded Entities - Cauble, Emily (Columbia Journal of Tax Law, 2015)
Publicly traded entities are generally treated as corporations for U.S. tax purposes. Under various exceptions, however, publicly traded entities may obtain special treatment if they earn predominately certain specified types of qualifying income. This Article examines potential rationales for granting special tax treatment to certain publicly traded entities. As the analysis in this Article will show, many of the potential rationales are unconvincing. In addition, to the extent that some rationales may be persuasive, the current rules are not designed in a way that best comports with these potential justifications. Therefore, reform is needed. To reform the current system, this Article proposes narrowing the scope of what may be classified as qualifying income so that special tax treatment is bestowed upon publicly traded entities only when warranted by underlying policy justifications. Specifically, this Article proposes that income that is classified as qualifying income under current law should not be classified in that manner unless it is earned by holding a publicly traded asset. In addition, current law grants favorable treatment to all income earned by a publicly traded entity if and only if the entity earns predominately qualifying income. This Article assesses whether tax law should, instead, grant special tax treatment to only qualifying income earned by a publicly traded entity, but with the special treatment applying regardless of whether the entity earns predominately qualifying income. Ultimately, this Article concludes that, on balance, concerns about complexity justify continuation of a regime under which beneficial treatment applies to all income earned by a publicly traded entity if and only if the entity earns predominately qualifying income, provided that the scope of what may be classified as qualifying income is narrowed in the manner proposed by this Article.